Three-dimensional kinetic Monte Carlo simulation of crystal growth from solution - Piana, Stefano; Gale, Julian (Elsevier Science BV, 2006)
The growth of urea crystals from water and methanol solutions has been studied with kinetic Monte Carlo simulations. Parameters for the simulations were derived from atomistic molecular dynamics simulations of the growth and dissolution of urea from water and methanol solutions. This approach allows the effect of solvation on the growth and dissolution kinetics to be fully included while extending the size of the simulation to the micrometre length scale and millisecond timescale.